Hereditary diffuse gastric cancer and lost cell polarity: a short path to cancer. (April 2008) - Humar, Bostjan; Guilford, Parry
The mechanisms that underlie the initiation of human cancer are poorly understood. Here, we describe the development of hereditary diffuse gastric cancer and argue that it arises from the disruption of the regenerative processes that are inherent to all epithelial tissues. This model supports the cancer stem cell hypothesis, in which tumors contain a subpopulation of cells with the key stem cell characteristics of capacity for self renewal, differentiation and limitless replication. We argue that epigenetic modifications induced by common environmental and physiological pressures are able to initiate this disruption. The carcinogenic effects of these modifications are potentially reversible through the use of epigenetic therapies such as DNA demethylating agents and histone deacetylation inhibitors.